Assay of anti-D using the Technicon AutoAnalyzer and the international standard anti-D typing serum. Issue 9 (December 1970) - Judd, W. J.; Jenkins, W. J.
Abstract : A method is described for the automated quantitation of the anti-D content of sera. This procedure is far more reproducible than current manual techniques. The use of the International Standard anti-D typing serum in the calibration of a working standard enables results to be expressed in μg/ml of antibody protein.